The Significance of Subculture among Malaysian Teenagers in 2015-2016 - Mohd Sukeri, Nur Farhana (Idealogy Journal; Vol 4 No 1 (2019): Idealogy Journal (April 2019)DO - 10.24191/idealogy.v4i1.273, 2019)
Letter to Editor - No Abstract